KNOWLEDGE, ATTITUDE, AND PRACTICES TOWARDS ALCOHOL ABUSE AMONG MEN AGED (20-45) YEARS IN KILHUBO VILLAGE, NGAMBA SUB COUNTY, BUNDIBUGYO DISTRICT. A CROSS-SECTIONAL STUDY. - Nabukenya, Sharifah; Kabakwa , Cosmas (Student's Journal of Health Research Africa, 2024)
Background This study aimed to assess "Knowledge, Attitude, and Practices on alcohol abuse among men in Kilhubo Village Bundibugyo District." The specific objectives were: to assess knowledge towards alcohol abuse among men aged 20-45 years, to assess attitude towards alcohol abuse among men aged 20-45 years, and to assess practices towards alcohol abuse among men aged 20- 45 years. Methodology A cross-sectional study design was used, and the target population was men aged 20-45 years. A sample size of 70 participants was used and data was obtained by using questionnaires, data were entered into, analyzed, and presented information pie charts, tables, and graphs. Results Findings from knowledge towards alcohol abuse among me aged 20-45 years revealed that 82%had ever heard of alcohol abuse and knew its side effects, most (65%) knew possible reasons why alcohol is abused outlining some as stress, ready availability, and 34% heard information about alcohol abuse from churches and community events. Regarding results from attitude, 92.9% had a negative attitude, and 76.7% had a positive attitude about alcohol abuse as abusers themselves. Findings from practice revealed that 57.1% drank locally brewed alcohol and 46% drank from bars. Conclusion Generally, the researcher concluded that the majority had ever heard of alcohol abuse and knew its side effects, knew possible reasons why alcohol was abused outlining some as stress, readily availability, heard information about alcohol abuse from churches and community events, had a negative attitude, those who had positive attitude alcohol abuse were abusers themselves, drunk locally brewed alcohol and drunk from bars. Recommendation The researcher recommended that the Ministry of Health should be in touch with the government together with the community members to increase awareness of the effects of alcohol and its outcomes.